2010
DOI: 10.1051/0004-6361/200913820
|View full text |Cite
|
Sign up to set email alerts
|

A serendipitous survey for variability amongst the massive stellar population of Westerlund 1

Abstract: Aims. Massive stars are known to demonstrate significant spectroscopic and photometric variability over a wide range of timescales. However the physical mechanisms driving this behaviour remain poorly understood. Westerlund 1 presents an ideal laboratory for studying these processes in a rich, coeval population of post-main sequence stars and we present a pathfinding study aimed at characterising their variability. Methods. To do this we utilised the large body of spectroscopic and photometric data that has ac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
88
2
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 54 publications
(101 citation statements)
references
References 83 publications
10
88
2
1
Order By: Relevance
“…However, to date no direct mass determination exists for a member of Wd1; as well as providing confirmation of the current understanding of the cluster derived from spectroscopic studies, this is of importance for confirming the high progenitor mass for the magnetar CXOU J164710.2-455216 that has been inferred from its membership of Wd1 (Muno et al 2006). In addition, the distribution of evolved stars in Wd1 offers the prospect of demanding tests for evolutionary models, with both the distribution of WR subtypes and the large number of cool hypergiants in both YHG and RSG phases at odds with current predictions (Clark et al 2010a).…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…However, to date no direct mass determination exists for a member of Wd1; as well as providing confirmation of the current understanding of the cluster derived from spectroscopic studies, this is of importance for confirming the high progenitor mass for the magnetar CXOU J164710.2-455216 that has been inferred from its membership of Wd1 (Muno et al 2006). In addition, the distribution of evolved stars in Wd1 offers the prospect of demanding tests for evolutionary models, with both the distribution of WR subtypes and the large number of cool hypergiants in both YHG and RSG phases at odds with current predictions (Clark et al 2010a).…”
Section: Introductionmentioning
confidence: 68%
“…therein; see also Clark et al 2010a;Negueruela et al 2010 population support a single burst of star formation at an age ∼5 Myr and a distance ∼5 kpc Negueruela et al 2010), with the identification of ∼O8V stars in the cluster (Clark et al, in prep. ) and a population of lower-luminosity late-O II−III stars just evolving off the MS both fully consistent with this derived age.…”
Section: Introductionmentioning
confidence: 80%
“…However, both studies are hampered by small sample sizes, which comprise stars which are known pulsators and hence radial velocity (RV) variables (cf. Clark et al 2010), potentially leading to significantly biased RV determinations. Finally Koumpia & Bonanos (2007) make multiple observations of four eclipsing binaries within Wd1 to determine their orbital parameters, from which mean values of v sys ∼ −40 ± 6 km s −1 are found (or v sys ∼ −45 ± 14 km s −1 depending on the assumptions made regarding the twin components of .…”
Section: Radial Velocity Surveymentioning
confidence: 99%
“…Of these, object D has been classified as an OB supergiant, and hence potentially the massive pre-SN companion we predict; classification spectroscopy of the remaining stars in combination with an RV survey of the full cluster population would be of considerable interest to determine if any of the three are indeed overluminous chemically peculiar runaway analogues to Wd1-5. Alternatively, if disruption is avoided, binaries containing magnetars should 7 By analogy to the optical properties of Of?p stars, Clark et al (2010) cited Wd1-24 as a possible highly magnetic star, based on the variable C iii+Pa 16 ∼8500 Å blend. However, further observations have revealed that this behaviour is instead due to a variable contribution from a late-O binary companion (Ritchie et al, in prep.).…”
Section: Implications For Magnetar Formationmentioning
confidence: 99%
“…Many B-type supergiants are reported to show spectroscopic and photometric variability (e.g., Fullerton et al 1996;Kaufer et al 1997Kaufer et al , 2006Lefever et al 2007;Clark et al 2010). In addition, spectral lines of B supergiants are found to be much wider than expected from pure stellar rotation.…”
Section: Introductionmentioning
confidence: 99%